2014
DOI: 10.30935/cedtech/6127
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Internet Addiction and Social Media Membership on University Students’ Psychological Capital

Abstract: How Internet addiction affects happiness of university students in terms of their cognitive and emotional resources was not adequately investigated. One of the inner resources of life satisfaction and happiness is defined as psychological capital (PsyCap), under the paradigm of positive psychology. PsyCap consists of four main sub-factors: hope, resilience, self-efficacy, and optimism. The major purpose of this study is to examine the role of Internet addiction and social media membership on PsyCap. The intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…If individuals lack psychological capital, they can't effectively cope with stressful events. They are still prone to suffer from negative emotions and behaviors, such as well-being (Poots and Cassidy, 2020), anxiety (Rahimnia et al, 2013), self-directed behavior (Choi, 2020), social media membership (Simsek and Sali, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…If individuals lack psychological capital, they can't effectively cope with stressful events. They are still prone to suffer from negative emotions and behaviors, such as well-being (Poots and Cassidy, 2020), anxiety (Rahimnia et al, 2013), self-directed behavior (Choi, 2020), social media membership (Simsek and Sali, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological capital is related to the achievements and well-being of individuals (Margaça et al, 2020), and it can be exploited like social resources (Luthans et al, 2006). Several studies have indicated that internet addiction is negatively correlated with psychological capital (Simsek and Sali, 2014). Problematic smartphone use also belongs to addiction behaviors (Zou et al, 2017), which also go against positive organizational behaviors and demonstrates performance.…”
Section: Introductionmentioning
confidence: 99%
“…Their study confirmed that PsyCap had some explanatory power for IA but did not clarify the specific mechanism between them. Simsek and Sali ( 25 ) found the same relationship between the two variables among a sample of 211 college students in Turkey. Khera's study on 130 Indian college students had similar findings ( 26 ).…”
Section: Introductionmentioning
confidence: 69%